Malaria Prevention Model Based on Kinship System Rakut Si Telu Orat Si Waluh - Sitepu, Rahmadani (JURNAL KESMAS DAN GIZI (JKG), 2025)
Malaria remains a global health problem and affects many tropical countries. Indonesia ranks second in Asia with the highest number of deaths from malaria. The Karo tribe has a kinship system of rakut si telu orat si waluh which is projected to be a community asset in implementing malaria prevention. This study is a qualitative study using in-depth interviews with malaria patients, three key informants, and eight relatives of malaria patients based on the rakut si telu orat si waluh system. The results found that malaria sufferers are often exposed to rain and activities outside the home at night, in the house there is a water reservoir, a lot of land in Rampah Village which was previously not taken care of so that the conversion of forests into gardens and residential areas, the community gives attention to malaria sufferers both in terms of informing the place of treatment and also facilitating sufferers to seek treatment, Karo tribal kinship based on rakut si telu orat si waluh also has a role in helping malaria treatment where each relative based on their kinship position has different tasks in helping sufferers treat malaria. Malaria prevention in the Karo community can be done by applying community capital based on the local perspectives of rakut si telu and orat si waluh. People involved in the rakut si telu and orat si waluh kinship systems have their respective roles in dealing with families suffering from malaria in terms of planning, prevention, handling and treatment.